From extraction to engagement: Post-mining transition and science communication in Lousal, Portugal - Affaki, M. S. (Extractive Industries and Society, 2026)
Former mining sites are increasingly tasked with mediating extractive pasts while engaging publics with contemporary sustainability challenges. Examining the case of the Lousal Cultural Complex – in Portugal's Alentejo, 140 km south of Lisbon – this paper highlights tensions in heritage interpretation, science communication, social engagement, and environmental responsibility. Drawing on documentary analysis, site visit, exhibition analysis, and interviews with institutional actors, the study assesses how mining history, environmental impacts and rehabilitation, and energy transition are communicated within the complex, across its permanent exhibitions and mediated activities. The Lousal Cultural Complex is a case that exemplifies both the possibilities of the integration of heritage reuse and science communication, and the curatorial challenges of balancing immersive and memorable engagement with the communication of just and transformative energy transitions. While the complex demonstrates substantial technical, cultural, scientific, and educational achievements, the findings reveal a marked narrative asymmetry: Narratives of extractive dependency and technological progress are embedded in permanent and interactive exhibitions, while social histories, environmental degradation, remediation limits, and post-extractive futures are communicated through incidental verbal interpretation, temporary exhibitions, or event-based programming. As a result, the potential to foster environmental citizenship is constrained, although possible to overcome by curatorial changes that engage publics with social histories and equip them with critical perspectives on consumption, circular economy, and mineral futures to promote just and green transitions.